2022
DOI: 10.1186/s40834-022-00181-0
|View full text |Cite
|
Sign up to set email alerts
|

Social consequences of COVID-19 on fertility preference consistency and contraceptive use among Nigerian women: insights from population-based data

Abstract: Background Emerging evidence from high income countries showed that the COVID-19 pandemic has had negative effects on population and reproductive health behaviour. This study provides a sub-Saharan Africa perspective by documenting the social consequences of COVID-19 and its relationship to fertility preference stability and modern contraceptive use in Nigeria. Method We analysed panel data collected by Performance Monitoring for Action in Nigeria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 36 publications
(51 reference statements)
5
10
0
Order By: Relevance
“…In line with our results, Akinyemi et al (2022) in a study on 774 married and non-pregnant women found that COVID-19 pandemic caused women to postpone their pregnancy, and this decision was related to age, higher education, and household food insecurity.…”
Section: Discussionsupporting
confidence: 91%
“…In line with our results, Akinyemi et al (2022) in a study on 774 married and non-pregnant women found that COVID-19 pandemic caused women to postpone their pregnancy, and this decision was related to age, higher education, and household food insecurity.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the findings reported here, in Nigeria, 8.8% of participants changed their minds about getting pregnant due to concerns about the COVID-19 pandemic [ 24 ]. In Italy, concerns about future economic problems were also similarly among the main reason for abandoning the intention to reproduce during the pandemic [ 16 ].…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, in Burkina Faso, a decrease in the desire to have children was reported in comparison to the pre-pandemic period [ 22 ]. In Nigeria, 8.8% also reported a lesser desire to reproduce due to concerns about the COVID-19 pandemic [ 24 ]. In Tehran, approximately three quarters of participants within a separate study similarly reported no intention to reproduce [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrates that the socio-demographic factors have been responsible in determining the fertility intentions among women seeking fertility at the time of crisis or uncertainty. The study conducted by (Akinyemi et al, 2022) among Nigerian women have similar results and stated that the fertility intentions have been influenced by "some social consequences of COVID-19" (p. 2). The findings of the study have been consistent with previous studies as fertility intention changes among women can be considered to be caused by the uncertain future due to pandemics or similar situations such as economic recession (Aassve et al, 2021), health and financial situation of a person (Hašková et al, 2019).…”
Section: Discussionmentioning
confidence: 74%
“…Since the outbreak of the COVID-19 pandemic, the people's livelihood has been affected, especially, in terms of reproductive health such as fertility preference and family planning (Akinyemi et al, 2022;Kahn et al, 2021;Naya et al, 2021;Roy et al, 2021). After the outbreak of the COVID-19 pandemic, people from all over the world, regardless of their ages and other background, were affected in various ways.…”
Section: Introductionmentioning
confidence: 99%